2015
DOI: 10.1115/1.4030350
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Analysis of Multiple Sensors for Industrial Gas Turbine Compressor Blade Health Monitoring

Abstract: This paper summarizes an analysis of data obtained from an instrumented compressor of an operational, heavy duty industrial gas turbine; the goal of the aforementioned analysis is to understand some of the fundamental drivers, which may lead to compressor blade vibration. Methodologies are needed to (1) understand the fundamental drivers of compressor blade vibration, (2) quantify the severity of “events,” which accelerate the likelihood of failure and reduce the remaining life of the blade, and (3) proactivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Kestner et al studied the correlations between different installed sensor types on blade vibrations. The authors used acoustic pressure, bearing vibration, tip timing and gas path measurement from an operating machine [14].…”
Section: Hot Gas Component Monitoringmentioning
confidence: 99%
“…Kestner et al studied the correlations between different installed sensor types on blade vibrations. The authors used acoustic pressure, bearing vibration, tip timing and gas path measurement from an operating machine [14].…”
Section: Hot Gas Component Monitoringmentioning
confidence: 99%
“…To avoid this and to increase the performance, safety and stability of gas turbine engines, several techniques have been developed in the last 50 years for Structural Health Monitoring (SHM) and Non-Destructive Testing (NDT) of turbomachinery engines blades [ 3 , 4 ]. Traditionally, a common system to validate the dynamics of rotating blades is the use of strain gauges [ 5 , 6 , 7 ]. However, while they have high accuracy and well established signal processing algorithms, strain gauges have limited lifetimes in high-temperature conditions, are intrusive, have complicated means of transmitting data from a rotating system and the provided information is limited to instrumented blades [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, while they have high accuracy and well established signal processing algorithms, strain gauges have limited lifetimes in high-temperature conditions, are intrusive, have complicated means of transmitting data from a rotating system and the provided information is limited to instrumented blades [ 4 ]. Unlike vibration, temperature and ultrasound-based techniques [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ], the Blade Tip-Timing (BTT) approach is one of the most advanced and versatile in situ techniques for axial turbomachinery blade dynamics measurements [ 15 , 16 , 17 ]. The principle of the BTT approach is based on the measurement of instantaneous blade tip deflection by detecting delays or advances in the arrival time of the blade tip at fixed angular positions [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hong and Huang [34] evaluated the health condition of the power transformer through the vibration correlation analysis. Kestner et al [35] analysed the correlations for sensors between the pressure measurements and bearing vibration measurements of gas turbine compressor from the view of harmonics. Recent studies suggested that the analytic representation can be another way to obtain time-resolved connectivity of signals.…”
Section: Introductionmentioning
confidence: 99%